Flow measurement in the southern coast of the Caspian Sea - Jamshidi, Siamak (Frontiers in Marine Science, 2024)
During storm events, a high level of correlation between the current and wind data was observed in the southern basin of the Caspian Sea during the 2017-2018 monitoring period. The measured current data indicated that the predominant directions were north (N) and northwest (NW). It was observed that strong gusts predominantly originated from the north (N) and northwest (NW) directions. Additionally, a smaller portion of the strong gusts was observed to come from the South-Southeast (S-SE) direction. These findings indicate that the prevailing wind patterns during the monitoring period were primarily from the north and northwest, with a lesser contribution from the South-Southeast direction. The current profiles observed during the monitoring period in the southern basin of the Caspian Sea were primarily influenced by the general circulation pattern of the region. This circulation pattern played a significant role in shaping the current profiles observed during the measurements. In terms of the surface current speed, the maximum recorded value was approximately 200 cm/s, which occurred in January. This indicates that there were instances of relatively high-speed currents in the southern basin of the Caspian Sea during that time. The evaluation of inter-annual variability in vertical structure and seawater temperature profiles during the monitoring period confirmed the presence of seasonal stratification in the water column of the southern basin of the Caspian Sea. This stratification was observed to consist of different layers, including the surface mixed layer, thermocline, and deep-water layers. The formation of these layers is indicative of the seasonal variations in temperature and density within the water column. The vertical changes in the water's physical parameters during the monitoring period revealed the formation of stratification in the southern basin of the Caspian Sea. In March, it was observed that the water temperature decreased from 11.5 o C at the surface to 8.5C at a depth of 100 m, indicating the presence of a temperature gradient. As the monitoring progressed into May, the stratification became stronger, with the surface water temperature reaching around 23C. By August, the surface layer of the sea water experienced a significant increase in temperature, reaching 29C.